2022
DOI: 10.1111/eip.13271
|View full text |Cite
|
Sign up to set email alerts
|

The effects of peer bullying and poverty on suicidality in Chinese left behind adolescents: The mediating role of psychotic‐like experiences

Abstract: Aim: This study investigated the influence of childhood adversity, such as peer bullying and socioeconomic status, on the suicidal behaviour of left-behind Chinese adolescents to determine whether psychotic-like experiences (PLEs) mediated the associations between these childhood adversities and suicidality; suicidal ideation (serious thoughts about taking one's own life), suicide plans, and suicide attempts.Methods: A representative group of rural adolescents (n = 3346) was recruited from 16 rural high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 120 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Similar to our results, it has been shown that PLEs are predictive of suicidal thoughts, even when controlling for sociodemographic variables and traumatic experiences [ 71 ]. Additionally, a history of childhood adversities, such as peer bullying, poverty, and left-behind status, has been found to increase suicide risk through the mediating effect of PLEs [ 72 ]. In line with our findings, depressive symptomatology has been associated with a history of CT and suicidality [ 73 ], and might mediate the relationship between a history of CT and suicidal risk [ 66 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, it has been shown that PLEs are predictive of suicidal thoughts, even when controlling for sociodemographic variables and traumatic experiences [ 71 ]. Additionally, a history of childhood adversities, such as peer bullying, poverty, and left-behind status, has been found to increase suicide risk through the mediating effect of PLEs [ 72 ]. In line with our findings, depressive symptomatology has been associated with a history of CT and suicidality [ 73 ], and might mediate the relationship between a history of CT and suicidal risk [ 66 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…One low group that has been the focus of research are families in rural areas; low SES parents often leave their children with relatives to nd work in more urban areas (Liu et al, 2016). In this context, low SES has been shown to be directly correlated with adolescents' depression and suicidal ideation (Li et al, 2022). However, our research took place in a urban areas, although the family's SES was low, the adolescents were unlikely to experience the long term absence of parents, and parents' availability and companionship itself is a kind of protection (Butler, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers' low SES is significantly associated with adolescents' emotional and conduct problems [22]. Low family SES has also been found to be associated with non-suicidal self-injury behaviors as well as the risk of suicide mediated by increased peer bullying among left-behind children [23,24].…”
Section: Family Socioeconomic Status (Ses) and Left-behind Children's...mentioning
confidence: 99%